Fiscal Incidence in Moldova : A Commitment to Equity Analysis - Cojocaru, Alexandru; Matytsin, Mikhail; Prohnitchi, Valeriu (World Bank, Washington, DC, 2019)
This paper uses methods developed by the Commitment to Equity Institute and data from the Household Budget Survey to assess the effects of government taxation and social spending on poverty and inequality in Moldova. The paper presents the first detailed distributional analysis of the tax and expenditure sides of the fiscal system, examining in particular the contribution of different taxes and transfers to poverty and inequality reduction in Moldova, as well as the cost-effectiveness of different taxes and transfers in achieving these poverty and inequality reduction goals. The analysis finds that the tax-benefit system in Moldova is quite pro-poor and has a significant effect on poverty and inequality, with the poverty reduction effect being stronger for lower poverty thresholds. Pensions provide much of the poverty-reducing effect, which is not surprising, given that in an aging society like Moldova, pensions are the main income source for many households. Direct transfers are also quite effective in reducing poverty and are also efficient, providing a relatively high degree of poverty reduction per dollar allocated to these programs, but their overall effect on poverty is muted by their small budgetary allocations.